2022
DOI: 10.1002/cmtd.202200031
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Process Digitalisation for Advanced Nanomaterial Syntheses

Abstract: Digitalisation and industry 4.0 are set to profoundly change the way chemical and materials discovery and development work. The integration of multiple enabling technologies such as flow synthesis, automation, analytics, and real-time reaction control lead to highly efficient, productive, data-driven discovery and synthetic protocols. For instance, the development of flow chemistry enables the fine control and automation of process parameters such as flow rates, temperature, and pressure, which inherently enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 93 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…Therefore, communicating intensified process descriptors could provide valuable insights at molecular and meso‐ and macroscales while increasing the volume, reliability, and variety of data. [ 75 ] For example, synthesis and processing of colloidal nanocrystals, with an experimental space ranging from 10 5 to 10 10 possible experimental conditions, are time‐ and material‐intensive tasks, using manual experimentation and batch reactors. In one example, Abdel‐Latif et al [ 76 ] reported intensification of the synthesis and bandgap tuning of inorganic metal halide perovskite nanocrystals using two integrated microfluidic reactors.…”
Section: Data‐centric Ammdmentioning
confidence: 99%
“…Therefore, communicating intensified process descriptors could provide valuable insights at molecular and meso‐ and macroscales while increasing the volume, reliability, and variety of data. [ 75 ] For example, synthesis and processing of colloidal nanocrystals, with an experimental space ranging from 10 5 to 10 10 possible experimental conditions, are time‐ and material‐intensive tasks, using manual experimentation and batch reactors. In one example, Abdel‐Latif et al [ 76 ] reported intensification of the synthesis and bandgap tuning of inorganic metal halide perovskite nanocrystals using two integrated microfluidic reactors.…”
Section: Data‐centric Ammdmentioning
confidence: 99%